2021
DOI: 10.3389/fsurg.2021.801718
|View full text |Cite
|
Sign up to set email alerts
|

Non-intubated Thoracoscopic Surgery—Pros and Cons

Abstract: Pulmonary resection by video-assisted thoracoscopic surgery with single-lung ventilation has become a standardized modality over the last decades. With the aim to reduce surgical stress during operation procedures, some have adopted a uniportal approach in pulmonary resection as an alternative to multiportal VATS. The ERAS program has been widely spread to achieve even better outcomes. In 2004, Pompeo reported the resection of pulmonary modules by conventional VATS under intravenous anesthesia without endotrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…[18] A large number of studies comparing intubated and nonintubated general anesthesia, especially in Asian countries, have shown that non-intubated thoracoscopic surgery can reduce the incidence of postoperative complications, shorten the length of hospital stay, and reduce perioperative mortality, indicating that non-intubated thoracoscopic surgery is a safe, effective and feasible anesthesia technique for thoracic surgery. [19] The necessary local anesthesia for non-intubation thoracoscopic surgery includes thoracic epidural anesthesia, cervical epidural anesthesia, paravertebral block, intercostal nerve block, local anesthesia at the incision site, local vagus nerve block, erector spinae plane block, serratus anterior plane block and pectoralis major nerve block. [20] Non-intubated thoracoscopic surgery can increase the incidence of hypercapnia and intraoperative cerebral oxygen saturation, reduce systemic inflammation, promote early postoperative activities, and accelerate the postoperative recovery of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[18] A large number of studies comparing intubated and nonintubated general anesthesia, especially in Asian countries, have shown that non-intubated thoracoscopic surgery can reduce the incidence of postoperative complications, shorten the length of hospital stay, and reduce perioperative mortality, indicating that non-intubated thoracoscopic surgery is a safe, effective and feasible anesthesia technique for thoracic surgery. [19] The necessary local anesthesia for non-intubation thoracoscopic surgery includes thoracic epidural anesthesia, cervical epidural anesthesia, paravertebral block, intercostal nerve block, local anesthesia at the incision site, local vagus nerve block, erector spinae plane block, serratus anterior plane block and pectoralis major nerve block. [20] Non-intubated thoracoscopic surgery can increase the incidence of hypercapnia and intraoperative cerebral oxygen saturation, reduce systemic inflammation, promote early postoperative activities, and accelerate the postoperative recovery of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, no patients in the current study experienced persistent hypoxemia during OLV, and the mean PaO 2 was measured to be 198.3 mmHg. Hypercapnia is a central element of non-intubated thoracic surgery related to hypoventilation due to sedation and OLV [ 18 ]. There is a risk of hypercapnic rebreathing effect due to paradoxical respiration that initially occurs and hypoventilation caused by the collapse of the operated lung [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…To guarantee both adequate access and visualization for non-intubated uniportal subxiphoid VATS thymectomy, it is necessary to create a bilateral iatrogenic pneumothorax. Opening both pleural cavities inevitably leads to (1) hypoventilation, (2) decrease of pulmonary perfusion, (3) decrease of functional residual capacity, and (4) hypercapnia [ 9 ]. An inserted laryngeal mask can mitigate these adverse effects by (1) administering a higher concentration of inspired oxygen, (2) enhancing the monitoring of end-tidal carbon dioxide and facilitating its removal, and (3) providing pressure-support ventilation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%